(3fbGFV LQjQ hGdaQRObs - (3nerYneQ Hf GdeKfi GdJjej HGdhdGA, GdHUQj, CHh YHjO GdfMhj,J (B209 (3g` s ((3eMeO Jbj Hf cga GdMGL YHOGdQGRb GdSGQLj s)
(3ChdgG (B:s
(3bGd CHhYHjOI hGSeg eYeQ(B: (3cGf GdSHH GdPj gGL GdJgGLj Hjf LQjQ Hf YWjg Hf MPjaI GdNWaj s
(3BNQgG (B:s
(3JMVhf bjkSG hdG JUHQhf dRHf GdMQhH hEVQGQgG (B((3hJdGgG bUjOI ddaQROb jeOM gTGe Hf YHOGdedc, hCHjGJ dCHj fhGS(B) s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde NGdj ef GdVHWs
(3Ydi ghGeTgG hHjf SWhQgG HYV GdTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs